High efficiency > 26 W diode end-pumped Alexandrite laser - Teppitaksak,A; Minassian,A; Thomas,GM; Damzen,MJ (Optics Express, 2014)
We show for the first time that multi-ten Watt operation of an Alexandrite laser can be achieved with direct red diode-pumping and with high efficiency. An investigation of diode end-pumped Alexandrite rod lasers demonstrates continuous-wave output power in excess of 26W, more than an order of magnitude higher than previous diode end-pumping systems, and slope efficiency 49%, the highest reported for a diode-pumped Alexandrite laser. Wavelength tuning from 730 to 792nm is demonstrated using self-seeding feedback from an external grating. Q-switched laser operation based on polarization-switching to a lower gain axis of Alexandrite has produced ~mJ-pulse energy at 1kHz pulse rate in fundamental TEM00 mode.